2018
DOI: 10.1186/s13104-018-3381-y
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate medical research in the Gulf Cooperation Council (GCC) countries: a descriptive study of the students’ perspective

Abstract: ObjectiveThere is a lack of research-oriented physicians in several Arab countries and especially in Gulf region countries. In this context, it is important to explore medical students’ perceptions and motivations towards research. The aim of the present study was to investigate research attitude, practices, and motivations among medical students from GCC countries.ResultsThere were 228 students who participated in this study (male 88, females 140). Thirty-eight percent of the students were participating from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 27 publications
5
19
0
3
Order By: Relevance
“…[22] Involving students in a funded research study, improving training in research methodology, training on how to present a paper at a scientific gathering, writing up and submitting a paper for publication providing the students with adequate time and student-centered teaching and learning strategies would encourage them to get involved in research activities. [15,35]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22] Involving students in a funded research study, improving training in research methodology, training on how to present a paper at a scientific gathering, writing up and submitting a paper for publication providing the students with adequate time and student-centered teaching and learning strategies would encourage them to get involved in research activities. [15,35]…”
Section: Discussionmentioning
confidence: 99%
“…A search of the medical literature revealed that several studies undertaken in Saudi Arabia for such purpose. [9][10][11][12][13][14][15] However, their results were limited only to a local university, region, or specific medical sciences college and its not possible to generalize their findings to other regions, such as Mecca region. There is a lack of research about medical sciences students' perception, barriers, and attitude toward scientific research in Mecca.…”
Section: Original Articlementioning
confidence: 99%
“…The GCC countries are contributing to medical research, which is evident by publications in peer-reviewed medical journals [ 30 ]. In the GCC countries, undergraduate medical students can partake in funded research, contribute to research activities, and attend local scientific conferences [ 31 ]. In Saudi Arabia, undergraduate medical students demonstrate positive research trends resulting from a research-oriented environment in the medical schools [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire used had 33 questions and was adopted from previously validated questionnaires by Sayedalamin et al (19) and Lloh et al (20).It consisted of 5 sections as below: Section l. Had 7 Questions about participants' demographics.…”
Section: Data Collection Toolmentioning
confidence: 99%